Excitotoxicity - An important target for neuroprotection - VIKAS VASANT PAWAR,; RACHANA D. SARAWADE, (International Journal of Pharma and Bio Sciences, 2019)
Glutamate is free amino acids that function as an Excitatory Neurotransmitter in the Central Nervous System (CNS). Excess Stimulation of Glutamate receptors i.e. NMDA(N-Methyl-D-Aspartate) receptor by Excitatory Neurotransmitter leading to number of deleterious consequences, such as impairment in Calcium efflux, Free radicals production, Mitochondrial dysfunction and Secondary Excitotoxicity. Excitotoxicity causes motor disorder such as Parkinson’s disease & non motor disorder such as Neuropathic pain. Neuroprotection is the only way to prevent Excitotoxicity. Therefore in this review, we summarize various Neuroprotecting agents preventing motor disorder like Parkinson’s disease & non motor disorder like Neuropathic pain caused due to Excitotoxocity.